Transitions From Hospitals to Skilled Nursing Facilities for Persons With Dementia: A Challenging Convergence of Patient and System-Level Needs - Andrea Gilmore‐Bykovskyi; Tonya Roberts; Barbara King; Korey A. Kennelty; Amy Kind (2016)
To describe skilled nursing facility (SNF) nurses' perspectives on the experiences and needs of persons with dementia (PwD) during hospital-to-SNF transitions and to identify factors related to the quality of these transitions. Grounded dimensional analysis study using individual and focus group interviews with nurses (N = 40) from 11 SNFs. Hospital-to-SNF transitions were largely described as distressing for PwD and their caregivers and dominated by dementia-related behavioral symptoms that were perceived as being purposely under-communicated by hospital personnel in discharge communications. SNF nurses described PwD as having unique transitional care needs, which primarily involved needing additional discharge preplanning to enable preparation of a tailored behavioral/social care plan and physical environment prior to transfer. SNF nurses identified inaccurate/limited hospital discharge communication regarding behavioral symptoms, short discharge timeframes, and limited nursing control over SNF admission decisions as factors that contributed to poorer-quality transitions producing increased risk for resident harm, rehospitalization, and negative resident/caregiver experiences. Engaged caregivers throughout the transition and the presence of high-quality discharge communication were identified as factors that improved the quality of transitions for PwD. Findings from this study provide important insight into factors that may influence transitional care quality during this highly vulnerable transition. Additional research is needed to explore the association between these factors and transitional care outcomes such as rehospitalization and caregiver stress. Future work should also explore strategies to improve inter-setting communication and care coordination for PwD exhibiting challenging behavioral symptoms.